Including cognitive aspects in multiple criteria decision analysis - Carneiro, João (2016)
Many multiple criteria decision analysis (MCDA) methods have been proposed over the last decades. Some of the most known methods share some similarities in the way they are used and configured. However, we live in a time of change and nowadays the decision-making process (especially when done in group) is even more demanding and dynamic. In thiswork,we propose aMCDAmethod that includes cognitive aspects (cognitive analytic process, CAP). By taking advantage of aspects such as expertise level, credibility and behaviour style of the decision-makers, we propose a method that relates these aspects with problem configurations (alternatives and criteria preferences) done by each decisionmaker. In this work, we evaluated the CAP in terms of configuration costs and the capability to enhance the quality of the decision. We have used the satisfaction level as a metric to compare our method with other known MCDA methods in literature (utility function, AHP and TOPSIS).Our method proved to be capable to achieve higher satisfaction levels compared to other MCDA methods, especially when the decision suggested by CAP is different from the one proposed by those methods.